STUDY OF HRCT CHEST FINDINGS AND SEVERITY SCORE IN COVID-19 PATIENTS AND ITS CORRELATION WITH CLINICAL AND LABORATORY PARAMETERS - DINESH M; SOMASEKHAR R; SRI RAMA MURTHY G; UMA MAHESWARA RAO M (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: High-resolution computed tomography (HRCT) refers to a CT scan that gives a more precise cross-section image of the lungs than a regular chest CT and chest X-ray. HRCT chest uses specific technologies for better image resolution with exquisite lung details ideal for assessment. This modality can be applied in diagnosing and grading severity in coronavirus disease 2019 (COVID-19) infection. HRCT is more sensitive and accurate in diagnosing diffuse lung disease. Since HRCT can detect even small nodules in the lungs, it can detect severe abnormalities at an early stage of the infection and help to plan appropriate treatment. The aim of the study was to study HRCT chest findings in patients with COVID-19 infection and correlation with clinical and laboratory parameters. Methods: This was a prospective and retrospective observational study done for duration of 1 year, that is, from June 2020 to May 2021 in the Department of Radio-diagnosis at Shri Sathya Sai Medical College and Research Institute, Tiruporur-Guduvancherry, Main Road, Ammapettai, Nellikuppam, Kancheepuram district on 235 COVID-19 positive patients. Results: The typical findings were ground glass opacity + reticular pattern (GGO +crazy paving) noted 50.2% moderate cases and 13.2% severe cases. The mild group (CT-SS of 1–8) consisted of 56 patients (23.83%), moderate group (CT-SS of 9–12) consisted of 143 (60.85%) patients where as severe group (CT-SS of >13) was composed of 36 (15.32%). Conclusion: HRCT chest plays an important role in early identification of the COVID-19 infection. HRCT severity score helps to the patients in guiding the treatment and monitor disease progression.